Predictive Value of Magnetic Resonance Imaging in Assessing Myometrial Invasion in Endometrial Cancer: Is Radiological Staging Sufficient for Planning Conservative Treatment?. Issue 7 (1st October 2010) - Cade, Thomas J.; Quinn, Michael A.; McNally, Orla M.; Neesham, Deborah; Pyman, Jan; Dobrotwir, Andrew
Abstract : Objectives: There has been an increasing interest in accurately assessing tumors preoperatively to plan appropriate surgery or, in some low-risk patients, conservative treatment. We wish to determine the accuracy of magnetic resonance imaging (MRI) in predicting myometrial invasion in endometrial cancer and whether it is a safe and suitable tool for planning conservative treatment. Materials and Methods: We compared MRI scans and final histopathologic diagnoses of 111 patients with endometrioid adenocarcinoma over a 6-year period at a major tertiary centre. Data were analyzed collectively and according to histological differentiation and types of MRI scans (1.5 vs 3 T). Outcomes were presence versus absence of myometrial invasion and recently revised International Federation of Gynecology and Obstetrics stage IA (up to 50% myometrial invasion) versus deep invasion. Results: Magnetic resonance imaging had a high negative predictive value for the presence of deep invasion (87% overall and 95% for grade 1 disease). However, although the positive predictive value for the presence of any myometrial invasion was high, negative predictive values were poor (35% for all grades and 46% for grade 1). There was no difference between 1.5- and 3-T scanning. Conclusions: Magnetic resonance imaging is a suitable screening tool for the presence of stage IA disease under the newly revised International Federation of Gynecology and Obstetrics staging system. The significance of this finding will depend on whether clinicians are willing to treat all grade 1 stage IA disease (under the revised system) as low risk and to deem selected patients in this group suitable for more conservative treatment.